DEVELOPMENT AND STUDY OF THIN-FILM MATERIALS FOR USE IN LITHIUM-ION MICROBATTERY - Serikkazyyeva, Assel (Nazarbayev University School of Engineering and Digital Sciences, 2022)
Li-ion microbatteries (LIMBs) are a hot topic for investigation due to the miniaturization of electronic devices. For better performance of the microbattery, it is really important to achieve good rate capability and stable cyclability of materials. Lithium metal (Li) one of the most attractive materials as an anode, with a high theoretical capacity (3860 mAh g1), low potential, and low density. However, the main obstacle with Li anode is uncontrollable dendritic growth during the charge and discharge process, high reactivity with moisture, and explosion during cycling. Tin is also one of the promising candidates, which has a high theoretical specific capacity (992 mAh/g) to compare with commercial graphite, better retention of capacity, and longer cyclability. However, Sn anodes usually suffer from the high expansion of volume, which leads to the structure collapse and causes capacity attenuation during the discharge/charge process. Lithium-tin (LixSn) alloy can also act as a negative electrode which can reduce the drawbacks of both Li and Sn materials due to the following advantages. Firstly, the LixSn alloy exhibits a much higher theoretical specific capacity of 788 mAh/g than commercial graphite anode. Secondly, LixSny alloy demonstrates much higher initial Coulombic efficiency than Sn anode. Also, due to the strong affinity between Li22Sn5 and metallic Li the ultrafast Li diffusion can be enabled. As well as the small difference between the potentials of the Li22Sn5 and Li (0.3V) served as a driving force of the Li diffusion. This structure of anode material can minimize the volume changes during stripping and plating by demonstrating lower overpotential. To the best of our knowledge, the LixSn alloy has not been studied before in microbatteries. The monolithic thin film can still experience the volume change and the amount of lithium is limited. From this point of view, the multilayered structure with the alternating LixSn and Li-rich layers can provide the highly diffusive media, buffer regions, and enough Li for reactions. This study reports about the novel multilayered thin-film anode based on LixSn alloy deposited by using magnetron sputtering and thermal evaporation techniques. Several thicknesses of multilayered anode were investigated (500, 1000, 1500 nm) in order to choose the optimal one. According to SEM, the alloy thin film has more round shape surface to compare with tin. Furthermore, the formation of an alloy was confirmed by XRD characterization. Electrochemical testing of prepared anodes with liquid electrolyte and lithium metal opposite electrode showed that the developed multilayered anode with an initial specific capacity of around 1100-1200 (mAh) and stable cyclability was tested during 100 cycles. Impedance spectroscopy showed lower resistance, that was further confirmed with lower overpotential of the investigated material. Finally, it can be concluded that the Li-Sn alloy-based anode material demonstrated the improved results, therefore can be promising anode material for next-generation LIMBs.
Keywords: type of access: gated access; Research Subject Categories::TECHNOLOGY; LIMBs; Li-ion microbatteries; thin-film materials